O protagonismo feminino: Comunidade Quilombola Sítio Arruda em Araripe - Ceará - Felipe, Márcia Leyla de Freitas Macêdo (Universidade do Vale do Rio dos Sinos, 2018)
The history of women was marked by a long trajectory of prejudices and difficulties, which is no different from the cearense Quilombola woman. The historical struggle of black women is for the guarantee of dignity and resistance against social and racial exclusion.The objective of this study was to analyze aspects of leadership and female protagonism in the Quilombola Community of Sítio Arruda, in the state of Ceará, as a collective and / or individual experience.The research was initially based on a bibliographical review where I made a survey of the trajectory of the black woman and the quilombola, analyzing their struggles, conquests and resistances. I presented the role of the black quilombola women as agents of the struggles for the regularization of their territory and for the maintenance of collective memory.I looked for conceptual elements to understand what quilombo means in the current Brazilian reality and how the quilombola communities organized themselves in the state of Ceará and the current situation of these communities.The research was developed in the Quilombola Community of Sítio Arruda, in the municipality of Araripe, in the state of Ceará, which already had its territory recognized by the National Institute of Colonization and Agrarian Reform (INCRA).I used oral history, as the main methodology and memory as the main source, interviewed women involved in various segments, such as education, community association, religiosity and political representation.It is noticed that, if the quilombola woman's space for action was previously related to the constant struggle for the reproduction of the family and community, today, this struggle takes on other senses, acting in the public-political space for the inclusion of the community in public policies and recognition of their land rights.I confirmed my hypothesis that these women have acted actively, as true protagonists, who contribute to the maintenance and development of these Quilombola communities.
Keywords: História oral; Quilombo; Mulher quilombola; Protagonismo feminino; Oral history; Quilombo; Quilombola woman; Female protagonism; ACCNPQ::Ciências Humanas::História